Perbaikan Sifat Geoteknik Tanah Lunak Lempung (CH) Terhadap Penambahan Semen Dan Limbah Bottom Ash - Aditia Siringoringo; Soewignjo Agus Nugroho; Syawal Satibi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The work built on the land which high plasticity clay (CH) that has a relatively low carrying capacity will have a short service life. To overcome this problem, efforts are made to improve the geotechnical properties of the soil by stabilizing using bottom ash (coal waste) and cement. The addition of this mixture aims to determine its effect in efforts to improve the physical and mechanical properties of high plasticity (CH) clay. The sample making in this research is based on the variation of bottom ash mixture 5%, 10%, 15% and the variation of the cement mixture is 3% and 5% of the dry weight of the soil. The UCS test was carried out as a reference to see the effect of using a mixture of bottom ash and cement. Testing of UCS samples was carried out based on curing time, with the following curing variations, without curing, 7 days and 28 days. Based on the results of the original soil UCS test, the Cu value is 10.55 kPa and the best mixed soil test value is in the variation of the soil mixture L-S5-BA15-C28 with a Cu value of 30.71 kPa. The conclusion from the research proved that the addition of a mixture of bottom ash and cement was able to increase the Cu value by 291.09% at 15% bottom ash content and 5% cement with a curing time of 28 days. Keywords : Bottom Ash, Cement, UCS, stabilization.